L’émergence d’une toponymie plurielle au Mali - Stéphanie Lima (L'Espace Politique)
In Mali, municipalities were created in the context of decentralization. Their creation reveals an original process of toponymic renewal at the local level. Between 1994 and 1996, the main characteristics of the new municipalities (size, boundaries, centre and name) have been debated and negotiated. The Malian government associated local populations with the process of demarcating new municipal boundaries, thus allowing for social and spatial representations to be taken into account. The respective balance between the internal logic of territorial demarcation and social representations differ according to place. In the Kayes region for example, the mobility and social networks that structure space have been integrated in the making of new, local toponyms. The names of the new municipalities vary from adhesion to the centre and adoption of the name of the chef-lieu to “neutral” toponyms. The nature of toponyms thus sheds light on the contrasted results of the national territorial restructuring.